1990
DOI: 10.1046/j.1468-2982.1990.1001017.x
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine in Migraine Prophylaxis: Efficacy and Tolerability of 5 mg and 10 mg Dose Levels

Abstract: The use of flunarizine, a drug which has proven its efficacy in migraine, is often associated with important side effects. The aim of this paper has been to check their incidence at different dose levels (5 mg vs 10 mg). Our data confirm the occurrence of important side effects (in particular weight gain); on the other hand, they emphasize the dose-dependency of the side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…The positive effect after drug discontinuation of a 6-month treatment seemed to last longer with flunarizine, although both medications significantly reduced migraine frequency and severity [65]. Previous studies found that 10 mg flunarizine may guarantee a more rapid efficacy than 5 mg [66] and it appears to be a very suitable agent for migraine prophylaxis and should be given for more than 2 months in order to obtain full effectiveness [67]. …”
Section: Discussionmentioning
confidence: 99%
“…The positive effect after drug discontinuation of a 6-month treatment seemed to last longer with flunarizine, although both medications significantly reduced migraine frequency and severity [65]. Previous studies found that 10 mg flunarizine may guarantee a more rapid efficacy than 5 mg [66] and it appears to be a very suitable agent for migraine prophylaxis and should be given for more than 2 months in order to obtain full effectiveness [67]. …”
Section: Discussionmentioning
confidence: 99%
“…Cinnarizine has a good antimigraine action although few studies have been carried out to investigate its efficacy in migraine [127, 128]. There are insufficient data supporting the efficacy of nimodipine and ciclandelate in migraine [129].…”
Section: Other Drugsmentioning
confidence: 99%
“…[2][3] The efficacy of Ca ++ antagonists, particularly of flunarizine, in the prophylaxis of migraine is well documented; flunarizine is usually prescribed at a dosage of 5-10 mg per day as a single evening dosage. [4][5][6][7][8][9] It is considered particularly effective in long term therapy 4 and in young subjects. [4][5][6] Both the efficacy and the side effects of flunarizine have been studied comparatively for the 5 and 10 mg dosages, and it has been noted that while the efficacy is similar, the side effects are reduced with the lower dosage.…”
Section: Introductionmentioning
confidence: 99%